The efficacy and safety of plerixafor in hematopoietic stem cell mobilization in patients with Non-Hodgkin lymphoma, multiple myeloma, and Hodgkin lymphoma who failed mobilization with granulocyte-colony-stimulating factor alone: A single-center experience - Girish Badarkhe; Radheshyam Naik (Indian Journal of Medical and Paediatric Oncology)
Introduction: Plerixafor is a CXCR4 antagonist which is administered along with granulocyte-colony-stimulating factor (G-CSF) to mobilize hematopoietic stem cells in patients with Non-Hodgkin lymphoma (NHL) or multiple myeloma (MM), who failed the mobilization with G-CSF alone. Methodology: This was a single-center, retrospective study of the efficacy of the plerixafor and G-CSF in 32 patients with NHL (n = 11), MM (n = 11), and Hodgkin lymphoma (HL) (n = 10) who failed mobilization with G-CSF alone. Results: A median number of 1.21 × 106, 1.32 × 106, and 6.73 × 106 CD34 + cells were mobilized in patients with MM, NHL, and HL, respectively. Overall, 31 (96.8%) patients mobilized more than 2 × 106 CD34 + stem cells and 21 (33.75%) patients mobilized more than 5 × 106 CD34 + stem cells. All 32 (100%) patients underwent hematopoietic stem cell transplantation. There were no adverse drug events reported. Conclusion: This retrospective study shows that plerixafor is an effective and safe mobilization agent in patients with NHL, MM, and HL who have failed mobilization with G-CSF alone.